Kemampuan Berpikir Reversible Siswa Kelas VIII dalam Menyelesaikan Soal Materi Penyajian Data - Ulfa Masamah; Firyal Alya Nabiela (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
This study aims to describe the reversible thinking ability of eighth-grade students in solving data presentation problems. Using a qualitative case study approach, the research involved two eighth-grade students from MTsN 2 Sumenep. Data were collected through a reversible thinking test and interviews and validated using method triangulation. Data analysis followed the data reduction, data presentation, and conclusion drawing. The results revealed that students’ reversible thinking consists of three aspects: forward reasoning, reciprocity reasoning, and negation reasoning. Students with high reversible thinking ability could trace two-way relationships between data and representations, while others still faced difficulties connecting numerical data with visual forms and reviewing their solutions logically. These findings suggest that reversible thinking involves not only procedural skills but also conceptual reflection on the relationship between data and results. Mathematics learning should therefore foster reflective and two-way thinking through activities using multiple representations.